Avaliação institucional de organizações de ensino superior: um estudo da abrangência semântica e formal da avaliação de desempenho em um modelo de autoavaliação de uma IFE paranaense - Alano, Elsi do Rocio Cardoso (2012)
The following work concerns the area of educational assessment form the field of Administration Studies. The main objective of this study was to analyze the semantic and formal scope of performance assessment within a self-assessment model developed by the Universidade Tecnológica do Paraná (UTFPR) [Technological University of Paraná]. The current legal policy scenario which structures the higher education in Brazil was chosen as the context of attainment of the self-assessment document, specifically since the implementation of SINAES regulation in 2004. Accordingly, a categorical content analysis was conducted based on a Multidimensional Model of Concept and Performance Assessment and supported by the CPA Institutional Assessment Report from UTFPR. The results from the content analysis proposed in this investigation showed positive and negative aspects with regards to the institutional self-assessment content, with special focus on: (i) several actions and activities were mentioned in the report, however not effectively assessed; (ii) the use of quantitative data which possibly originated from documents prior to the implementation of the CPA Comissão Própria de Autoavaliação) [Self-assessment Commission]; (iii) the lack of qualitative assessment, which demonstrates the impossibility of inferring (based on the data presented) the effectiveness level of the actions from a perspective of multiple stakeholders and, with regards to the quantitative assessment, the lack of data referring to the expected excellence level or standard; (iv) the prioritization of data aggregated to multiple levels of assessment (according to SINAES request); (v) the multiple theoretical approaches used to assess the results; that is, assessment of outputs, inputs, processes an in less frequent cases, the perception of one of the stakeholders.